Desenvolvimento de biorreator de tambor rotativo em escala de bancada - Polidoro, Tomás Augusto (My University, 2014)
In this work, details on the assembling of a solid state cultivation system, whose main component is a bench scale rotating-drum bioreactor, are described. The bioreactor was built in refractory glass and has an approximate volume of 6.2 liters. To assemble the equipment, the following aspects have been studied: geometry of the bioreactor; control of frequency and period of agitation; moistening, warming and controlling of the inlet air flux; mixing of cultivation medium; determination and control of medium temperature; sample withdrawn. The developed system was evaluated, being the cultivation of the pectinolytic enzymeproducing microorganism Aspergillus niger T0005/007-2 used as the model process. The fermentative tests were carried out in a medium containing wheat-straw as solid support and were used to evaluate the effects of three main parameters agitation, mass of cultivation medium and medium temperature on the cell growth and the production of endopolygalacturonase (endo-PG) by A. niger. For agitation of the solid medium, three modes were compared: no agitation; agitation of 1 rpm for 5 minutes each 2 hours; agitation for 1 hour and 55 minutes, each 2 hours. The second mode of agitation led to the best cell growth, 81 mg.g-1, and to endo-PG activity of approximately 80 U.g-1, similar to that obtained with the static system. With the third mode of agitation occurred, apparently, some damage to fungus mycelium and inferior results were achieved. The evaluation of the mass of cultivation medium on the process was done by loading the reactor with masses that result in the occupation of 30, 45 and 60% of the working volume of the bioreactor. With respect to the cell growth, the best result was attained with the smallest load of medium, whereas the intermediate load resulted in the highest endo-PG activity, 107.2 U.g-1. In the experiments on the influence of the temperature on the cultivation of A. niger, the largest endo-PG activity (80.6 U.g-1) was obtained in a process condition that allowed that the temperature reached values close to 45ºC. When the medium temperature was controlled at 30ºC, the endo-PG activity was substantially lower, 46.4 U.g-1. In the tests with the model process, no clearly positive influence of agitation on the production of endo-PG was observed. From the temperature-controlled experiments however, it is possible to suggest that endo-PG formation is favored by a stress condition for the microorganism, represented in this case by medium temperatures over 40ºC, since the optimal temperatures for A. niger growth is found in the range of 28 to 34ºC. This result disagrees from what is generically described in the specialized literature for the solid state cultivations, being this fact an example of the importance of having a small-scale rotating-drum bioreactor as a basic equipment for fundamental studies on that type of fermentative process. Additionally, the fact of the reactor body being built on glass allows the inspection of the internal space of the rotating drum and to observe the effects of agitation on the cultivation medium.
Neste trabalho, são descritos os detalhes da montagem de um sistema de cultivo microbiano em estado sólido, cujo elemento principal é um biorreator de tambor rotativo em escala de bancada, com casco em vidro refratário com aproximadamente 6,2 litros de volume. A montagem do equipamento exigiu estudos para a definição dos seguintes aspectos: geometria do reator; controle de frequência e período de agitação; umidificação, aquecimento e controle do fluxo do ar injetado no sistema; mistura do meio de cultivo; medição e controle da temperatura do meio; retirada de amostras. O sistema desenvolvido foi avaliado, tendo como processo fermentativo modelo o cultivo de Aspergillus niger T0005/007-2, microrganismo produtor de enzimas pectinolíticas. Os testes foram feitos em um meio contendo farelo de trigo como suporte sólido, avaliando-se a influência de três parâmetros principais agitação, massa de meio de cultivo e temperatura do meio sobre o crescimento celular e a produção de endo-poligalacturonase (PG) por A. niger. Três formas de agitação do meio sólido foram comparadas: sem agitação; agitação a 1 rpm por 5 minutos a cada duas horas; agitação a 1 rpm por 1 hora e 55 minutos a cada duas horas. A segunda forma de agitação levou ao melhor crescimento celular, 81 mg.g-1, e a atividade de endo-PG da ordem de 80 U.g-1, semelhante ao estimado com o sistema estático. Com a terceira forma de agitação, aparentemente houve dano ao micélio fúngico e, com isso, resultados inferiores foram alcançados. A avaliação do efeito da massa de meio de cultivo sobre o processo foi feita com cargas crescentes de meio que resultaram na ocupação de 30, 45 e 60 % do volume útil do reator. Quanto ao crescimento celular, o melhor resultado foi alcançado com a menor carga de meio, enquanto que a carga intermediária resultou no mais alto título enzimático final, 107,2 U.g-1. Nos experimentos sobre a influência da temperatura sobre o cultivo de A. niger, a maior atividade enzimática (80,6 U.g-1) foi obtida numa condição de trabalho que permitiu que a temperatura do meio atingisse valores da ordem de 45ºC. Com o meio mantido a 30ºC, a atividade enzimática máxima foi substancialmente mais baixa, 46,4 U.g-1. Nos testes realizados com o processo modelo, não se verificou uma clara influência positiva da agitação sobre a produção de endo-PG. Entretanto, a partir dos experimentos com temperatura controlada, é possível sugerir que a formação de endo-PG é favorecida por uma condição de estresse para o microrganismo, no caso representado por temperaturas do meio acima de 40ºC, visto que a temperatura ideal de crescimento de A. niger encontra-se na faixa de 28 a 34ºC. Este resultado, que discorda do que é genericamente descrito na literatura especializada sobre cultivos em estado sólido, é um exemplo da importância de dispor-se de um biorreator de tambor rotativo de pequena escala como equipamento básico para a realização de estudos fundamentais a respeito deste tipo de processo. Adicionalmente, o fato de o corpo do reator ser construído em vidro permite a visualização do espaço interno do tambor rotativo e observar o efeito da agitação sobre o meio de cultivo.
Keywords: MICROBIOLOGIA; Microbiologia industrial - Equipamento e acessórios; Biorreatores; Fermentação; Enzimas - Aplicações industriais; Industrial microbiology - Equipment and supplies; Bioreactors; Fermentation; Enzymes - Industrial applications